2018
DOI: 10.4108/eai.29-5-2018.154807
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Actionable Knowledge from Domestic Violence Discourses on Social Media

Abstract: Domestic Violence (DV) is considered as big social issue and there exists a strong relationship between DV and health impacts of the public. Existing research studies have focused on social media to track and analyse real world events like emerging trends, natural disasters, user sentiment analysis, political opinions, and health care. However there is less attention given on social welfare issues like DV and its impact on public health. Recently, the victims of DV turned to social media platforms to express t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Helpfulness on Online Support Communities Helpfulness has been studied in online support communities where peers can offer help and support to one another. These communities often center around a shared life situation such as chronic health conditions (Subramani and O'Connor, 2018;Green et al, 2020) and family bereavement (Schotanus-Dijkstra et al, 2014;Paulus and Varga, 2015). Several factors were emphasized in common: Peers were found more helpful when they are emotionally warm and compassionate, give others choice on a solution, willing to accept others' perspectives and experiences, practice active listeningby paraphrasing, asking questions and reflecting feelings, give pertinent advice/insights to help others to solve their problem, as well as share similar experiences (Chuang and Yang, 2012;Schotanus-Dijkstra et al, 2014;Paulus and Varga, 2015;Subramani and O'Connor, 2018;McKiernan et al, 2018;Green et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Helpfulness on Online Support Communities Helpfulness has been studied in online support communities where peers can offer help and support to one another. These communities often center around a shared life situation such as chronic health conditions (Subramani and O'Connor, 2018;Green et al, 2020) and family bereavement (Schotanus-Dijkstra et al, 2014;Paulus and Varga, 2015). Several factors were emphasized in common: Peers were found more helpful when they are emotionally warm and compassionate, give others choice on a solution, willing to accept others' perspectives and experiences, practice active listeningby paraphrasing, asking questions and reflecting feelings, give pertinent advice/insights to help others to solve their problem, as well as share similar experiences (Chuang and Yang, 2012;Schotanus-Dijkstra et al, 2014;Paulus and Varga, 2015;Subramani and O'Connor, 2018;McKiernan et al, 2018;Green et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Helpfulness has been extensively studied based on exchanges in online support communities (Chuang and Yang, 2012; Schotanus-Dijkstra et al, 2014; Paulus and Varga, 2015;Subramani and O'Connor, 2018;McKiernan et al, 2018;Green et al, 2020). These studies found that helpfulness is associated with various characteristics such as emotional warmth, relevant knowledge, willingness to understand, empowering choice, active listening as well as sharing of similar experiences.…”
Section: Introductionmentioning
confidence: 99%
“…In the U.S., 20 people suffer from DV every minute. The consequences of DV for victims are often severe, far-reaching, and long-lasting, causing major health (including both physical and mental health), welfare, and economic damages (Subramani, 2019). DV is the 12th leading cause of years of life lost.…”
Section: Domestic Violencementioning
confidence: 99%
“…Subramani et al proposed a novel framework in [10] to model and discover different types of domestic violence in the public domain and ultimately provide actionable knowledge. Their method uses topic detection to turn Twitter data into actionable knowledge.…”
Section: Related Workmentioning
confidence: 99%